Intelligence Science I: Second IFIP TC 12 International Conference, ICIS 2017, Shanghai, China, October 25-28, 2017, Proceedings - Shi, Zhongzhi; Goertzel, Ben; Feng, Jiali (Intelligence Science I Second IFIP TC 12 International Conference, ICIS 2017, Shanghai, China, October 25-28, 2017, Proceedings, 2017)
This book constitutes the refereed proceedings of the Second International Conference on Intelligence Science, ICIS 2017, held in Shanghai, China, in October 2017.The 38 full papers and 9 short papers presented were carefully reviewed and selected from 82 submissions.